More trouble ahead; is gene therapy coming of age? - Tan, P; Janes, SE; Handa, A; Friend, P (2008)
BACKGROUND: A recent incident, the halting of a Phase I/II trial utilising an adeno-associated vector, highlights the fact that there are more hurdles to overcome prior to a full realisation of gene therapy in the clinical arena. METHODS: The sources of information used to prepare the paper were obtained through published work on Pubmed/Medline and materials published on the US/UK governmental agency websites. RESULTS/CONCLUSION: Over the years, two fatal incidents associated with viral vector usage have been reported. Viral vectors used as carriers for gene therapy have failed in safety trials on two occasions. Also, the human immune response and the oncogenic property of the vectors have restricted the advancement of gene therapy as a therapeutic tool. Nonetheless, gene therapy has now progressed from its infancy 'proof of concept' stage, to the next stage in which we try to overcome the problems associated with therapeutic application. However, this progression has been slow as more and more setbacks have occurred. This calls for a new perspective and radical thinking about future vector development.